Corpo vivente e cyberspace: la dimensione hyletica nella costituzione della conoscenza - Ales Bello, Angela (B@belonline, 2020)
When one hears terms like the “living” or “lived” body and hyletics, one immediately thinks of Edmund Husserl, especially since he identifies the hyletic dimension as the first layer of the constitution of the human being. This layer is closely linked to corporeity. Herein lies the novelty of the phenomenological method. In my paper I examine the relationship between the living body and the virtual space which is linked up with phantasy. Particularly interesting is the use of virtual space in geometry where the cyberspace can be a tool to explain its main notions. In any case one may observe also that the virtual space must not be privileged with the risk to forget the real space and the importance of one’s corporeity.